Posted by **Kevin** on Sunday, February 13, 2011 at 5:07pm.

I need to prove this

σ(hat)^2(x,y) = (1/n) Σ (Xi - X (bar) ) Yi

using

σ(hat)^2(x,y)= (1/n) Σ (Xi - X(bar)) (Yi-Y(bar))

and

X(bar)= (1/n) Σ Xi

σ(hat)^2 (x,y) is the estimator of covariance

## Answer this Question

## Related Questions

- Statistics Hypothsis testing - Am I using the 2-sample T test or ANOVA? Please ...
- Statistics - r^2 the corelation squared measures how well the y hat is than just...
- Statistics - test the claim that μ1 = μ2 Two samples are randomly ...
- Geomtric Series - I need to find the equations of the following, using Σ (...
- physics - if theta is the angle between unit vectors A bar and B bar, then (1-A ...
- Physics - The cylindrical bar in the figure has a total length L=1.2 m, a ...
- Statistics - Four pairs of data yield r=0.942 and the regression equation y-hat=...
- Chemistry - Why do we have these two equations: ΔH° = ΣD (bond broken...
- physics - Hello everyone, I need help with this question: A bartender slides a ...
- Physics - A bar of aluminum (bar A) is in thermal contact with a bar of iron (...